Kedudukan Akad Tijarah dan Akad Tabarru’ Dalam Asuransi Syariah - Farid Fathony Ashal (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2016)
This study aims to analyze the concept of the contract that adopted in Takaful. The contract must conform with fatwa DSN (National Sharia Council) No. 21 of the Takaful. According this fatwa Takaful consists of two contract, the tijarah contract and tabarru’ contract. The both contracts are analyzed with a Hadith that forbid the double contract in one transaction. The method used in this study with the conceptual approach (library research) to examine the theory of the jurists' of the various schools. This research is expected to provide a clear understanding of the interpretation of the legal text that sharih to muamalah and to avoid the mistakes that plunged astray against contemporary transactions.